2014
DOI: 10.1017/jmo.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Leader feedback and knowledge sharing: A regulatory focus theory perspective

Abstract: This paper investigates the impact of leader feedback on followers’ knowledge-sharing behavior through a regulatory focus theory perspective. Data were collected through an experiment with 129 college students. Results showed that compared with leader’s prevention feedback style and negative feedback valence, promotion style and positive feedback valence inspire employee knowledge-sharing behavior better. These two positive relationships are mediated by promotion situational regulatory focus. The negative rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 50 publications
(73 reference statements)
2
23
0
Order By: Relevance
“…Finally, this study also introduced the regulatory focus theory to explore the boundary conditions between the prosocial motivation and knowledge sharing of employees, thus enriching the research on the relationship between regulatory focus and knowledge sharing. When analyzing the relationship between regulatory focus and knowledge sharing, existing literature focused on the direct role of regulatory focus on knowledge sharing (Li et al, 2014b ) and examined the moderating role of regulatory focus between organizational elements and knowledge sharing (Ju et al, 2019 ). However, little attention has been paid to the moderating role of regulatory focus in the relationship between individual motivational factors and knowledge sharing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study also introduced the regulatory focus theory to explore the boundary conditions between the prosocial motivation and knowledge sharing of employees, thus enriching the research on the relationship between regulatory focus and knowledge sharing. When analyzing the relationship between regulatory focus and knowledge sharing, existing literature focused on the direct role of regulatory focus on knowledge sharing (Li et al, 2014b ) and examined the moderating role of regulatory focus between organizational elements and knowledge sharing (Ju et al, 2019 ). However, little attention has been paid to the moderating role of regulatory focus in the relationship between individual motivational factors and knowledge sharing.…”
Section: Discussionmentioning
confidence: 99%
“…From those who have investigated perceptions of knowledge sharing, the role of subjective norms emerges as affecting intentions to share knowledge (Young, 2014; Zhang & Ng, 2013). In particular, Li, Liu, Shang, and Xi (2014) found leader feedback, relating to promotion and positive encouragement, to be vital in enabling knowledge sharing in the organization. However, Ford and Staples (2006) suggest that, in addition to normative conditions of encouragement and sharing, a perceived value of knowledge can positively relate to sharing behavior.…”
Section: Background and Conceptual Modelmentioning
confidence: 99%
“…In particular, Li, Liu, Shang, & Xi (2014) found leader feedback, relating to promotion and positive encouragement, to be vital in enabling knowledge sharing in the organisation. However, Ford and Staples (2006) suggest that, in addition to normative conditions of encouragement and sharing, a perceived value of knowledge can positively relate to sharing behaviour.…”
mentioning
confidence: 99%
“…To sum up, better organizational outcomes can be gained by KS (Sharifkhani et al , 2016). Hence, understanding how organizational and individual factors influence KS is essential and beneficial (Li et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on the importance of leadership in facilitating KS (Sharifkhani et al , 2016), but few studies have investigated the relationship between leadership and KS so far, even though leaders are essential in shaping KS behavior by signaling appropriate and normative followers’ behaviors and guiding the formation of KS norms and climate (Li et al , 2014). Empirical evidence has shown that both transformational and transactional leadership forces have positive effects on KS, as with empowering leadership (Li et al , 2014). On the other hand, Wickramasinghe and Widyaratne (2012) have not found evidence of a positive and significant relationship between team leader support and KS.…”
Section: Introductionmentioning
confidence: 99%